Analysis of Political Education Programmes on the Quality of Voter Participation in the 2024 General Election - Noprianto; Sastro M. Wantu; Lucyane Djaafar (Journal of Law, Politic and Humanities, 2024)
This study aims to analyse political education programs and their impact on the level of voter participation in the 2024 General Election in Banggai Regency. Using a qualitative method with a case study approach, data was collected through observation, interviews, and documentation. Primary data was obtained from the General Election Commission, Election Supervisory Agency, political parties, National and Political Unity, and voters in Banggai Regency. Secondary data was obtained from journals, books, and reports on the implementation of the 2024 elections. The results showed that political education programs such as voter education socialisation. The results of this programme have implications for voter participation, which is reflected in the increase in turnout in the 2024 elections to 80.83%, compared to 79.47% in the 2019 elections. Nonetheless, several factors such as voters' limited cognitive, affective and evaluative abilities, as well as limited access to information and economic instability, proved to be obstacles affecting political participation. This study recommends that election administrators improve the effectiveness of political education programmes by actively involving voters in these programmes, in order to encourage more optimal participation.